A rare case of left sided trans-mediastinal herniation of right lung, its management and review of literature - Prasad, Dinesh; Shah, Kesha C. (International Surgery Journal, 2020)
Mediastinal herniation can occur either due to traction as in the case of lung shrinkage in tuberculosis and chronic bronchostenosis or pulsion as a result of hydropneumothorax, empyema necessitans, and chronic infective etiology. We are reporting a case of left sided trans-mediastinal herniation of right lung in a patient with underlying right pulmonary tuberculosis, presenting with empyema thoracis. Empyema thoracis in pulmonary tuberculosis may either be a cause of trans-mediastinal herniation of lung or be a co-existent condition when the herniation occurs due to hydropneumothorax. Due to the presence of infection in pleural space, a prosthesis cannot be used. Due to the proximity of hernia sac to heart and major vessels, its plication is better avoided. Hence, treatment of such a case can be done by applying negative pressure for a few post-operative days till the dead space has been obliterated. Trans-mediastinal herniation of lung with underlying empyema thoracis requiring decortication can be successfully treated with the application of intermittent strong negative pressure (after completing decortication) in the pleaural cavity near mediastinum to gradually deliver the herniated lung to its normal position followed by application of negative pressure in the post op period through one of the ICDTs (intercostal drainage tubes) to avoid unnecessary post-operative complications or reherniation.